2005
DOI: 10.18806/tesl.v23i1.75
|View full text |Cite
|
Sign up to set email alerts
|

Developing Cognitive Academic Language Proficiency: The Journey

Abstract: This study tracks the development of cognitive academic language proficiency of 47 academically competent high school ESL learners of differing age on arrival (AOA) who received instructed ESL support and one comparison group of six young arrivals who received little if any ESL support during their educational experiences. Although intake and outcome measures appear similar on the surface for all 47 students, variability in the subscores of the outcomes measure provided the catalyst for taking a closer look at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Roessingh, Kover and Watt (2005) found differences between the levels of CALP proficiency of young age arrivals in bilingual education programmes in Canada and older age arrivals. In the Canadian immigrant context, they found that younger age arrivals and older age arrivals made statistically significant improvements in reading proficiency in English as a result of educational interventions, but that 'The older-arriving group used more cognitive strategies (contextual guessing) and were better able to deploy higher-order thinking skills to solve problems (making inferences)' (Roessingh et al, 2005: 19).…”
Section: Research Question 1: Comparison Of Contextsmentioning
confidence: 81%
See 1 more Smart Citation
“…Roessingh, Kover and Watt (2005) found differences between the levels of CALP proficiency of young age arrivals in bilingual education programmes in Canada and older age arrivals. In the Canadian immigrant context, they found that younger age arrivals and older age arrivals made statistically significant improvements in reading proficiency in English as a result of educational interventions, but that 'The older-arriving group used more cognitive strategies (contextual guessing) and were better able to deploy higher-order thinking skills to solve problems (making inferences)' (Roessingh et al, 2005: 19).…”
Section: Research Question 1: Comparison Of Contextsmentioning
confidence: 81%
“…Secondly, following from the above argument, the possible effect of higher-order thinking skills and the use of better developed cognitive strategies in higher-education students (compared to school pupils) should be considered for the multilingual, South African context. Findings from Roessingh et al (2005) indicate a possible advantage for higher-education learners if the appropriate educational strategies were to be designed and implemented.…”
Section: What Are the Differences And Similarities Between The Contexmentioning
confidence: 99%
“…There is a significant body of research exploring the impact of language testing on teachers and classrooms (e.g., Chapman and Snyder, 2000;Cheng, 2005;Qi, 2007) and the socio-political systems surrounding them (e.g., McNamara and Roever, 2006;Shohamy, 2001); however, impact on the "ultimate stakeholder", the individual language learner, has received far less attention (Cheng et al, 2010, p. 222). Additionally, although there is an impressive body of research focused on young adolescent learners in the literature on language teaching and learning (e.g., Guilloteaux and Dörnyei, 2008;Roessingh et al 2005;Swain and Lapkin, 1995), very few studies have focused on these learners in relation to their language assessment environment , as older adolescents, adults, and young English language learners (under 12 years) have tended to occupy researcher interest.…”
Section: Assessment Practices and Adolescent Motivationmentioning
confidence: 99%
“…Test form T, used in this study, has Kuder-Richardson Formula 20 reliability coefficient .93 (Maria & Hughes, 2008). The instrument is often administered to non-native speakers of English (Kamhi-Stein, 1998;Roessingh, Kover, & Watt, 2005).…”
Section: Definitions and Operational Terms Reading Comprehensionmentioning
confidence: 99%
“…English reading comprehension was measured by standardized instrument, Level AR of the Gates-MacGinitie reading test, often administered to non-native speakers of English (Kamhi-Stein, 1998;Roessingh, Kover, & Watt, 2005). Test form T, used in this study, has Kuder-Richardson Formula 20 reliability coefficient .93 (Maria & Hughes, 2008).…”
Section: Research Question 2: Predictors Of English Reading Comprehenmentioning
confidence: 99%